Utvärdering av motorsågskörkortet - Fernlund, Erik (SLU/School for Forest Management, 2016)
The accident rates associated with chainsaw operation have been unacceptably high for a long time. This has been due to insufficient knowledge of working techniques and low risk awareness. A mandatory requirement to obtain documented knowledge in chainsaw operation has recently been introduced. These requirements apply to anyone not working on their own forest estate. The intention is to prevent injuries and improve operating techniques. The purpose of the study was to investigate opinions among chainsaw operators regarding these new work requirements. From those who had received chainsaw licenses during 2014 a sample of 500 were randomly selected and asked to complete questionnaire. The results of the survey showed that many users find that the requirement should apply to everyone who uses chainsaw. All categories of chainsaw users stated that the three elements as they become more security awareness was, planning of felling tree with respect to risks, felling implementation and control, and take down failure felled trees.